The Impact of the COVID-19 Pandemic on Low Income Households in the Philippines : Impending Human Capital Crisis - Cho, Yoonyoung; Avalos, Jorge; Kawasoe, Yasuhiro; Johnson, Douglas; Rodriguez, Ruth (World Bank, Washington, DC, 2021)
The Coronavirus (COVID-19) pandemic has caused a dramatic disruption in the delivery of education and health services in the Philippines. With school closures and challenges in the delivery of distance learning, students learning losses are expected to be enormous. Meanwhile, the health system is strained under the challenge of management of Coronavirus (COVID-19) cases which likely crowd out the delivery of essential health services. This note, a third note of the series using the Coronavirus (COVID-19) Low Income Household Panel and Economic (HOPE) Survey, investigates the impact of the pandemic on education and health behaviors as well as other welfare indicators of low-income households in the Philippines.